RETRACTED: Simulation of a synchronous hydrodynamic system based on a throttle flow divider of a non-valve type - Rybak Alexander; Meskhi Besarion; Pelipenko Alexey; Serdyukova Yuliya; Teplyakova Svetlana; Marchenko Maxim (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001